Pengaruh Pengungkapan Emisi Karbon, Board Diversity Dan Capital Expenditure Terhadap Nilai Perusahaan - Rahman, Ahmad Auliya; Ismanto, Hadi (Universitas Islam Kadiri, 2025)
This study aims to analyze the effect of carbon emission disclosure, board diversity and capital expenditure on company value. This study uses secondary data sources in the form of annual reports and sustainability of manufacturing companies taken from the company's official website. The research population to be observed is all manufacturing companies listed on the Indonesia Stock Exchange as many as 166 and the observation year is 2021 to 2023. The sampling technique used in this study is the purposive sampling technique of 80 companies that meet the criteria, so that the number of observations is 240 for 3 years. The analysis technique uses panel data regression analysis and hypothesis testing uses the t-test. The results of the study obtained that the carbon emission disclosure variable has a negative and significant effect on company value. Meanwhile, the board diversity variable has no effect on company value. In addition, the capital expenditure variable has a positive and significant effect on company value.